Comparative Cytogenetics Analysis of Chlamys farreri, Patinopecten yessoensis, and Argopecten irradians with C0t-1 DNA by Fluorescence In Situ Hybridization. (7th July 2011) - Hu, Li-Ping; Shang, Wen-Cong; Sun, Yan; Wang, Shan; Ren, Xiao-Liang; Huang, Xiao-Ting; Bao, Zhen-Min
Abstract : The chromosomes of Chlamys farreri, Patinopecten yessoensis, and Argopecten irradians were studied by FISH using C. farreri C0 t -1 DNA probes. The results showed that C0 t -1 DNA signals spread on all chromosomes in the three scallops, whereas signal density and intensity were different strikingly. Clustering brighter signals presented in the centromeric and telomeric regions of most C. farreri chromosomes, and in the centromeric or pericentromeric regions of several P. yessoensis chromosomes. Comparative analysis of the mapping indicated a relatively higher homology in the repetitive DNA sequences of the genome between C. farreri and P. yessoensis than that between C. farreri and A. irradians . In addition, FISH showed that the distribution of C0 t -1 DNA clustering signals in C. farreri displayed completely similar signal bands between homologous chromosomes. Based on the C0 t -1 DNA fluorescent bands, a more exact karyotype of C. farreri has been obtained. In this study, the comparative analysis based on C0 t -1 DNA provides a new insight into the chromosomal reconstructions during the evolution process, and it is helpful for understanding an important source of genomic diversity, species relationships, and genome evolution.